Physico-chemical composition of hydrosoluble extract of sunflower almonds prepared under different operational conditions (Research, Society and Development, 2020)
The objective was to evaluate the physicochemical composition of water-soluble extract of sunflower almonds prepared under different operational conditions. Shelled sunflower almonds were purchased from local businesses in the city of Pombal, Paraíba, Brazil. The extracts were prepared in three different times of contact with water (10, 20 and 30 minutes) and in three different temperatures (60, 70 and 80 ° C) and the extracts obtained were analyzed according to the physical-chemical characterization, determining the moisture, ash, pH, protein and lipid content. The analysis of the interactions of the independent variables were studied through planning in a factorial scheme, using a matrix of type 22 + 3, resulting in 7 experiments. The best responses from the planning and / or process optimization matrix were obtained for moisture, pH, proteins and lipids. It is noted that for these parameters, the contact time variable had significant effects, where the extracts prepared with 30 minutes of contact of the almonds with water used in the processing showed the best results. Regarding the ash content, they did not show significant effects on the pre-established conditions of time and temperature according to the planning matrix.